Methane emission from rice production as affected by rice variety selection - Thi Bach Thuong Vo; Wassmann, Reiner; Van Nha Duong; Sander, Björn Ole; Asch, Folkard (2021)
This field experiment in the Vietnamese Mekong Delta in 2020 applied the closed chamber method to quantify methane emissions of 20 varieties in combination with Alternate Wetting and Drying (AWD), an irrigation management proven to reduce GHG emissions.